Kompetenčni profil gradbenega inženirja - Mikoš, Matjaž (Gradbeni vestnik, 2021)
The renovation of the higher education study system in Slovenia according to the Bologna scheme (three-cycle study) is already well behind us and the experience with the renovation is known. The article discusses the academic education of civil engineers in Slovenia with a focus on the required competencies to be acquired during the studies in order to become certified civil engineers, in accordance with the renewed construction legislation. The starting point for the analysis is the German Reference Framework, as prepared by the Accreditation Association of Study Programs in Civil Engineering in Germany. The mentioned German reference framework is compared with the valid competencies as prepared for certified engineers under the new Construction Act in Slovenia by the Slovenian Chamber of Engineers. The German reference framework refers only to the academic first-cycle study, while the Slovenian reference framework refers to the completed master degree. However, a comparison is possible, especially if someone in Slovenia offers a single-cycle master study program in the field of civil engineering, and designs the first three years in accordance with the German Reference Framework, which is more detailed than the Slovenian Reference Framework.
Keywords: certified engineers; civil engineers; construction legislation; gradbena zakonodaja; gradbeni inženirji; kompetence; references; terciarno izobraževanje; tertiary education